Barriers and facilitators to childhood obesity prevention among culturally and linguistically diverse (CALD) communities in Victoria, Australia. (28th February 2017) - Cyril, Sheila; Nicholson, Jan M.; Agho, Kingsley; Polonsky, Michael; Renzaho, Andre M.
Abstract: Objective: Childhood obesity is rising among culturally and linguistically diverse (CALD) groups who show poor engagement in obesity prevention initiatives. We examined the barriers and facilitators to the engagement of CALD communities in obesity prevention initiatives. Methods: We used the nominal group technique to collect data from 39 participants from Vietnamese, Burmese, African, Afghani and Indian origins living in disadvantaged areas of Victoria, Australia. Data analysis revealed ranked priorities for barriers and facilitators for CALD community engagement in obesity prevention initiatives. Results: CALD parents identified key barriers as being: competing priorities in the post‐migration settlement phase; language, cultural and program accessibility barriers; low levels of food and health literacy; junk food advertisement targeting children; and lack of mandatory weight checks for schoolchildren. Key facilitators emerged as: bicultural playgroup leaders; ethnic community groups; and school‐based healthy lunch box initiatives. Conclusion: This study has identified several policy recommendations including: the implementation of robust food taxation policies; consistent control of food advertising targeting children; improving CALD health literacy using bicultural workers; and matching health promotional materials with CALD community literacy levels. Implications for Public Health: These recommendations can directly influence public health policy to improve the engagement of CALD communities in obesity prevention services and ultimately reduce the widening obesity disparities in Australia.